Thiol-X chemistries in polymer and materials science - Lowe, Andrew B. 1972-; Bowman, Christopher N. 1967- (RSC polymer chemistry series, 2013)
Thiol-X chemistries are already well established techniques, but it is only recently that they have been exploited for the functionalization and synthesis of polymers and other materials. As such, information on these techniques is scattered across the literature and Thiol-X Chemistries in Polymer and Materials Science is the first book to compile work specifically focussing on the application of thiol-based chemistries in materials design and synthesis. The book introduces the various thiol-X chemistries currently available and applications where they have been successfully used, including examples of 'click' processes, in polymerizations, polymer synthesis, and polymer modification. Short 'how to' sections within the chapters also provide general experimental techniques to employ the various chemistries described.